Pengaruh Film-Induced Tourism Terhadap Niat Kunjungan Dan Merekomendasikan Kunjungan Ke Destinasi Yang Dimediasi Oleh Keterlibatan Wisatawan Terhadap Film - Syahla Karima Musfha; Heri Puspito Diyah Setiyorini (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of film-induced tourism on visit intention and destination recommendation intention, mediated by tourist engagement, using the Netflix series "Gadis Kretek" as the research object. The novelty of this study lies in the empirical examination of tourist engagement as a mediating mechanism within the film-induced tourism ecosystem on digital streaming platforms in Indonesia, a relationship that remains insufficiently explored in existing literature. A quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) was applied to 300 respondents who had watched the series. Results indicate that film-induced tourism exerts a very strong influence on tourist engagement (β = 0.910, p < 0.001), which subsequently significantly affects visit intention and recommendation intention (β = 0.342, p < 0.001). The direct effect of film-induced tourism on behavioral intention was non-significant (β = 0.087, p = 0.155), confirming that tourist engagement operates as a full mediator (VAF = 100%). These findings establish that exposure to streaming content does not automatically generate behavioral intentions without a deep psychological engagement process, thereby substantially enriching the theoretical framework of film-induced tourism.